Illustration of the Impedance Behaviour of Extremely Low-Profile Coupled Shorted-Patches Antennas for UHF RFID of People - Milan Svanda; Milan Polivka (International Journal of Antennas and Propagation)
The recently introduced coupled shorted-patches technique for the design of extremely low-profile UHF RFID tag antennas is used to illustrate the flexibility of selected feeding methods for tuning the antenna input impedance for the complex values required for matching with typical RFID chips. We present parametric studies of the impedance behaviour of dipole-excited and directly excited antennas designed for radiofrequency identification of people in the European UHF frequency band. Our study can significantly facilitate the design of this class of on-body tag antennas.